PARTISIPASI PEMUKA MASYARAKAT DALAM PENGELOLAAN PERPUSTAKAAN DESA - Daeng Ayub; Anindita Yulisman; Muhammad Jais (STKIP Pesisir Selatan, 2022)
Community participation in development in the village also determines the strength of an existing program, and determines the success of a program, including the establishment of village infrastructure. The Village Library is an important point that needs to be taken seriously in its establishment, use and even in its management. The entire process can be carried out by the community, one of which is library management. In its management, the village library requires the participation of the community. This community in question is the community leaders in the village. Parties from the village government took part in the establishment of the village library in Segati Village. In the management of the village library, the involvement of community leaders is impossible if it does not exist, which community leaders in this village are very accepting and have hope in the infrastructure of this village. With the strength of community leaders, there is a great hope in the management of this village library. This research was conducted with the aim of knowing and describing the participation of community leaders in the management of village libraries in Desa Segati Kecamatan Langgam Kabupaten Pelalawan. The method in this research is descriptive research with a qualitative approach. The object of the research is participation, community leaders, and village libraries and the research subjects are community leaders, totaling 4 (four) people. Participation in ideas and social participation which is given as a closeness of heart is the participation that is most often carried out by community leaders. This is because participation is a very easy, flexible and timeless form of participation. In addition, labor participation, skill participation is participation carried out by community leaders but still has limited time and opportunities due to differences in work and opportunities from each community leader in Desa Segati Kecamatan Langgam Kabupaten Pelalawan. Meanwhile, property participation has been carried out by several community leaders indirectly.